Hubungan Kadar Kolesterol Darah dan Hipertensi dengan Kejadian Stroke Di RSUD Ulin Banjarmasin - Theresia Jamini; Yunita yunita; Yulyanti Yulyanti; Candra Kusuma Negara (HB PRESS, 2020)
Stroke or Cerebrovascular disease according to the World Health Organization (WHO) is a clinical sign that develops rapidly due to focal or global brain dysfunction due to blockage or rupture of blood vessels in the brain with symptoms lasting 24 hours or more. Risk factors for stroke are related to the condition of a person's health status, namely hypercholesterolemia (excess cholesterol levels) and hypertension (high blood pressure) Methods: A descriptive analytic correlative observational study with a cross sectional approach. The number of samples was 62 people who were taken using the Slovin formula. Statistical analysis used the Sperman Rank test and Linear Regression test. Results: By using the Sperman Rank test, it was found that there was a significant relationship between blood cholesterol levels and the incidence of stroke in statistical tests with a p value of 0.004 (p <0.05), there was a significant relationship between hypertension with the incidence of stroke in statistical tests with p value 0.031 (p <0.05) there is no significant relationship between blood cholesterol levels and hypertension in statistical tests with p value 0.129 (p> 0.05) and by using Linear Regression Test obtained that the relationship between blood cholesterol levels with a mean value of 0.453 and hypertension with a mean value of 0.994 so that the most dominant with the incidence of stroke is hypertension. blood cholesterol and hypertension, and the relationship between blood cholesterol levels and hypertension with incidence The most dominant stroke is hypertension.